Facebook reactions in the context of politics and social issues: a systematic literature review - Anwar, Sawood; Giglietto, Fabio (Frontiers in Sociology, 2024)
In February 2016, Facebook launched five "Reactions" (i.e., Love, Haha, Wow, Sad, and anger) for users to emote their experiences with the posts, which were an extension of the "Like" button and were edited versions of Unicode emojis. Scholars used them to investigate user behavior and situation-based current topics to measure various aspects of socioeconomic and psychological topics. This literature review focuses on "Facebook reactions," examines the literature, and serves as a comprehensive and cumulative approach, summarizing the existing literature and research articles, scattered under different names. However, to get comparable results within broader classification and themes, we seek how "Facebook reactions" play a role in different or comparable topics and their results.Articles were collected using Google Scholar and other search engines. We used the keywords "Facebook" and "Reaction," with a combination of different key phrases and Boolean operators. Seventy-three articles are taken into consideration from 2016-2023. Matrix and Reference lists were scanned with different topics classified date-wise. The articles cover a wide range of topics/information such as Political News, Far-right and Extremist Parties, Racism, and Hate speech with COVID-19. Our Findings reveal nuanced patterns of the reaction distribution based on the topics. The positive reaction dominates articles related to lifestyle and entertainment, while the articles addressing sociopolitical issues elicit a wider range of reactions, including negative sentiments. Moreover, we observe that emotional content tends to get higher reaction volumes regardless of sentiment.